The Decomposition Process Of Food Waste For Organic Fertilizer Production At Engineering Campus, Universiti Sains Malaysia - Idrus, Mohd Firdaus Ahmad (Universiti Sains Malaysia, 2022)
Composting technology is one of the most effective ways to minimize solid waste. In this study, the technique chosen was aerobic composting. Aerobics composting was used as the approach for this investigation. Aerobic composting is a method of decomposing organic waste that employs oxygen gas. Because of the presence of oxygen, this composting process is particularly efficient in decreasing the foul odour caused by ammonia gas and hydrogen sulphide. This, in turn, can lessen the environmental impact of pollutants. The composting method utilized in this study is drum composting, in which food waste and yard waste are composted in a bin/composter. This study has been divided into three stages, namely Stages 1, 2 and 3. Stage 1 is a study to determine the physical and chemical properties of yard waste such as moisture content, pH, and carbon to nitrogen (C: N) ratio. In Stage 2, a composting study was performed on a mixture of food and yard waste in a 1: 1 ratio. At this Stage, 6 liters of rumen fluid were also added as a stimulant in speeding up the composting process in the composter. During the composting process, the compost will go through periodic monitoring in terms of temperature, moisture content, pH and C: N ratio. In Stage 3, a composting study was performed on a mixture of food and yard waste with a ratio of 2: 1. At this stage, 3 liters of rumen fluid were also added to the composter. During the composting process, the compost will go through periodic monitoring as well, namely monitoring in terms of temperature, moisture content, pH and C: N ratio. The resulting compost was also tested for nutrient content (nitrogen and potassium) using the ICP method and heavy metal content (Fe, Zn, Cu, Cd) was tested using the AAS method. Stage 3 is an upgrade Stage from Stage 2. So, the results obtained in Stage 3 are better than in Stage 2. The results showed that there was an increase in temperature to the thermophilic phase (> 45 ° C) at Stage 3. The highest temperature recorded was 46.87 ° C. In Stage 2, a high-temperature increase could not be produced where the compost of this stage only recorded 43.4 ° C. The C: N ratio produced in Stage 3 is less than 20: 1 which is better than the C: N ratio produced in Stage 2. The resulting C: N ratio in Stage 2 is more than 20: 1. In terms of the percentage of moisture content, Stage 3 recorded a better percentage of 61.23% compared to 73% recorded in Stage 2. The change in pH for compost in Stage 3 is also the desired pH which is more significant than pH 7 which is 7.45 compared to the compost produced in Stage 2 which is considered too alkaline which is 8.81. The results in terms of nutrients and heavy metals at Stage 3 are also considered good and can be used as an enhancer to the soil. Based on the rough observation, it was found that the compost produced in Stage 3 is more suitable for use than the compost produced in Stage 2. This is due to, Stage 3 compost having the characteristics of mature compost compared to Stage 2 compost. Mature compost has a darker color, smells like soil and is porous. So, these characteristics can be seen in Stage 3 compost but not in Stage 2 compost. The production rate of organic fertilizer from 1m3 of waste for stage 2 is 0.033 m3 and for stage 3 is 0.059 m3.